Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
(6,8)
Step-by-step explanation:
2x + y = 20
6x - 5y = -4
Multiply the first equation by -3
-3(2x + y) = -3*20
-6x -3y = -60
Add this to the second equation
-6x-3y = -60
6x - 5y = -4
--------------------
-8y = -64
Divide each side by -8
-8y/-8 = -64/-8
y = 8
Now find x
2x+y = 20
2x +8 = 20
2x+8-8 = 20-8
2x = 12
Divide by 2
2x/2 = 12/2
x = 6
(6,8)
Answer:
(6,8)
Step-by-step explanation:
2x + y = 20 (1)
6x - 5y = -4 (2)
Multiplying EQ 1 by 5
=> 5(2x + y) = 5(20)
=> 10x + 5y = 100 (3)
On adding 2 and 3
=> 6x - 5y + 10x + 5y = -4 + 100
=> 16x = 96
=> x = 96/16
=> x = 6
From 1
=> 2(6) + y = 20
=> 12 + y = 20
=> y = 20 - 12
=> y = 8
In pair
(x,y) = (6,8)
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.